Improved quantification of Fusarium pseudograminearum (Fusarium crown rot) using qPCR measurement of infection in multi-species winter cereal experiments - Milgate, Andrew; Baxter, Brad; Simpfendorfer, Steven; Herdina,; Giblot-Ducray, Daniele; Yang, Nannan; Orchard, Beverly; Ovenden, Ben (Frontiers in Plant Science, 2023)
Fusarium crown rot (FCR) causes significant grain yield loss in winter cereals around the world. Breeding for resistance and/or tolerance to FCR has been slow with relatively limited success. In this study, multi-species experiments were used to demonstrate an improved method to quantify FCR infection levels at plant maturity using quantitative PCR (qPCR), as well as the genotype yield retention using residual regression deviation. Using qPCR to measure FCR infection allowed a higher degree of resolution between genotypes than traditional visual stem basal browning assessments. The results were consistent across three environments with different levels of disease expression. The improved measure of FCR infection along with genotype yield retention allows for partitioning of both tolerance and partial resistance. Together these methods offer new insights into FCR partial resistance and its relative importance to tolerance in bread wheat and barley. This new approach offers a more robust, unbiased way to select for both FCR traits within breeding programs.